Comply or evade: factors influencing private enterprises’ basic old-age insurance responsibilities - Xu, Wanli; Ma, Haosen; Peng, Zihao; Peng, Caodie; Qian, Xihong (Frontiers in Public Health, 2024)
Introduction Private enterprises are playing an increasingly important role in production and employment in China. However, due to less regulation and a stronger profit motivation than state-owned enterprises with more standardized management, a considerable portion of these private enterprises fall short of fulfilling their basic responsibilities for government-mandated old-age insurance. Methods This study establishes a comprehensive research framework aimed at delving into the precise factors contributing to the lax adherence of private enterprises to their basic old-age insurance obligations. This framework takes into account a range of factors, including enterprise profitability, the external environmental context (specifically the level of regional development), and internal organizational dynamics (such as the presence of labor unions and workers’ congresses). To validate this framework, empirical data from a substantial sample of 3,123 private enterprises, which were part of the 10th Chinese Private Enterprise Survey (CPES), were utilized. This study employs the stepwise multiple regression analysis and conducts robustness tests to ensure the model’s effectiveness. Results Enterprise profitability, regional development levels, and the existence of labor unions all wield a positive influence on basic old-age insurance coverage that private enterprises extend to their workforce. Moreover, an intriguing aspect emerges: the developmental stage of the region, as well as the presence of labor unions exercise a negative moderating effect on the relationship between enterprise profitability and the coverage rate of basic old-age insurance. In essence, this implies that the basic old-age insurance coverage rate for private enterprises operating in well-developed regions and those with established labor unions is relatively insulated from fluctuations in profitability. Discussion To increase the participation rate of private enterprises’ basic old-age insurance, it is important to improve the overall development environment for private enterprises, enhance internal organizational mechanisms, and strengthen regulatory oversight of enterprises in various regions.